Textura y Estrés: las aplicaciones olvidadas de la Difracción de Rayos X en materiales - Larrañaga Varga, Aitor (2020)
X-ray crystallography result constitutes a fundamental analytical technique for the thorough study of the crystalline structure of materials. Despite to its enormous relevance at both scientific and industrial level, the popularization of its advanced analysis methodologies has been insufficient up today. Therefore, in this work we show different application possibilities using the X-ray diffraction, very useful in order to obtain in some cases critical information from our materials.